BASIS OF OPTIMAL MINERAL INORGANIC WASTE PROCESSING METHODS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Inorganic waste materials are important part of total waste amount in the world and must be utilized in the best optimal way. Among the inorganic materials there are such different materials as quarry byproducts from screening, settling ponds, baghouse fines, coal fly ash, sewage sludge ash and so on. Any proposal to incorporate a waste or by product materials into technologies requires engineering evaluation. At first, it is necessary to analyze chemical composition of waste materials, then- structure and particle size distribution, chemical and physical properties. The paper presents results of analyzes and collection of chemical and structural characteristics mentioned above inorganic materials and by-products. The presented data will serve for next investigations in finding better way for their utilization.